PEMBERDAYAAN KOMUNITAS IBU PKK MELALUI EDUKASI PENGOLAHAN MOCHITUL (MOCHI BEKATUL) SEBAGAI UPAYA PEMANFAATAN HASIL SAMPING KOMODITAS PERTANIAN MASYARAKAT DI DESA PEDURUNGAN, KABUPATEN PEMALANG - Amar, Danu; Afiani, Nurida; Asiyah, Nuri; Adifa, Retno Egha; Amalia, Ritchie; Kurniawati, Ika; Indriyani, Tantri Nur; Amanda, Risa; Yulianti, Rina Dewi; Rosyid, Ghufron; Sari, Icha Puspita; Fajri, Rifqi Nurul; Izzah, Lathifatul (Universitas Negeri Makassar, 2024)
One of the largest crops in Pedurungan Village is rice. The milling process produces by-products in the form of husks and bran. Currently, rice by-products are only used for animal feed. Bran is still considered waste, when in fact it has many health benefits. Bran is rich in nutrients, both macro and micronutrients. Bran has antioxidant properties, chemopreventive activity, and hypocholastrolemic activity. With the large amount of nutritional content and benefits of bran, it is a disadvantage if it is not used further. For this reason, KKN students in community service brought the idea of using bran into processed food. Bran in the form of flour is used as a substitute in making mochi. With the addition of bran, it will produce mochi products with higher nutritional content than conventional mochi. The method of making mochi uses trial and error. The target of the service program is the PKK women of Pedurungan Village in the form of material socialization. The material information presented included the benefits of bran, the nutritional content of bran, and a video on how to make bran mochi. Through socialization, information about nutrient-rich by-products can be used to process food, which can be conveyed to the community. In addition, this innovation can also make awareness of ingredients that are often overlooked and motivation to develop ideas and creativity with local food ingredients that are around.